Unique epitope–antibody interactions in the intrinsically disordered proteoglycan-like domain of human carbonic anhydrase IX defined by high-resolution NMR combined with yeast surface display - Feng Ni; Cunle Wu; Ping Xu; Ping Wang; Yves Fortin; Melanie Arbour; Luke Masson; Denis L’Abbé; Andrea Acel; Mylene Gosselin; Anne E.G. Lenferink (mAbs)
Carbonic anhydrase (CA)-IX is an extracellular enzyme that is essential in the adaptation of tumor cells to their increasingly more hypoxic and acidic microenvironment. Within the family of carbonic anhydrases, CA-IX is unique in that it is the only CA with an N-terminal intrinsically disordered region (IDR) containing a proteoglycan (PG)-like domain. This PG-like IDR has been described to be instrumental in CA-IX’s enzyme activity, as well as tumor cell motility and invasion. We have characterized the antibody–epitope interactions of two novel and unique antibodies (11H9 and 12H8) that are specific for the human CA-IX’s IDR. Binding interactions of these antibodies to the intact IDR were studied by surface plasmon resonance and high-resolution nuclear magnetic resonance (NMR) spectroscopy, while the specific epitopes were determined by both NMR and yeast surface display (YSD). Our data show that 12H8 binds to the N-terminus of CA-IX, while 11H9 has a high affinity for an epitope located in the central region of the IDR containing three GEEDLP repeats in a manner that is different from the previously described M75 antibody. Titration NMR spectroscopy using CA-IX’s entire IDR in addition identified a secondary epitope of 11H9 at the beginning of the PG-like domain that remains exposed and available for further binding events after the engagement at its primary epitope at the center of the PG-like domain. Transverse relaxation optimized NMR spectroscopy of 11H9-F(Ab) in complex with the CA-IX IDR outlines structural rigidification of a linear epitope, while the rest of the IDR remains largely unstructured upon complex formation. This study illustrates how high-resolution NMR and YSD are used as complementary tools for a comprehensive characterization of antibody–epitope interactions involving intrinsically unstructured antigen domains with highly repetitive sequences.